DIGITAL AESTHETICS: A PHILOSOPHICAL ANALYSIS (Universal International Scientific Journal, 2026)
This article examines the new forms of aesthetic perception emerging as a result of the rapid development of digital technologies in the 21st century and their philosophical essence. Digital aesthetics is interpreted as an important scientific direction aimed at deeply analyzing the impact of technological tools on the perception, evaluation and aesthetic creation process of modern man. The research reveals how the traditional categories of aesthetic thinking - beauty, harmony, tragedy and humor - are undergoing transformation in the digital and virtual environment. The article analyzes the specific features of aesthetic experience in digital space using historical-comparative, epistemological and systematic approaches. The theoretical basis of the research is J. Baudrillard's views on simulacrum and hyperreality, J. Lipovetsky's concept of postmodern visuality, and the idea of ​​\u200b\u200b"digital man" put forward by Sh. Turkle. These philosophical approaches shed light on the aesthetic content of digital images and visual forms, their relationship with reality. The results of the study serve to determine the place of the concept of digital aesthetics in modern philosophy and cultural studies, and to establish criteria for evaluating aesthetic values ​​​​formed in a technological environment. The article is of theoretical and practical importance for researchers dealing with the problems of digital culture, philosophy and art
Keywords: aesthetics; digital aesthetics; philosophy